2010
DOI: 10.1061/(asce)hy.1943-7900.0000153
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Flow through Idealized Emergent Vegetation

Abstract: This paper presents results of several large-eddy simulations ͑LES͒ of turbulent flow in an open channel through staggered arrays of rigid, emergent cylinders, which can be regarded as idealized vegetation. In this study, two cylinder Reynolds numbers, R D = 1 , 340 and R D = 500, and three vegetation densities are considered. The LES of the lowest density and at R D = 1 , 340 corresponds to a recently completed laboratory experiment, the data of which is used to validate the simulations. Fairly good agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
138
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(162 citation statements)
references
References 28 publications
18
138
0
Order By: Relevance
“…7a, b) indicate that the turbulence predominantly follows the expected Kolmogorov decay rate, indicating that all the scales of interest lie within the inertial subrange and that the model accurately reproduces the turbulent processes with this range, with minimal impact of numerical diffusion or energy dissipation due to the SGS model [81,82]. As discussed in Sect.…”
Section: Spectral and Wavelet Analysismentioning
confidence: 73%
“…7a, b) indicate that the turbulence predominantly follows the expected Kolmogorov decay rate, indicating that all the scales of interest lie within the inertial subrange and that the model accurately reproduces the turbulent processes with this range, with minimal impact of numerical diffusion or energy dissipation due to the SGS model [81,82]. As discussed in Sect.…”
Section: Spectral and Wavelet Analysismentioning
confidence: 73%
“…Furthermore, using this Although, the initial application of the model has been on relatively simple canopies, the new methodology presented here enables investigation of flow through complex canopies across a wide range of plant forms. This is essential as natural macrophyte canopies do not conform to the idealised canopy configurations traditionally studied (Dunn et al 1996, Stoesser et al 2010 and it is possible that different turbulent processes dominate in the nonidealised case. The application of the N-pendula model permits the investigation of turbulent energy extraction, and thus the effect on the mean flow conditions through realistic canopies.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work has developed this analysis and begun to use larger domains, enabling larger patch-scale analysis at stem-scale resolution. Stoesser et al (2010) undertook LES experiments on a patch of emergent vegetation using a combination of high resolution Cartesian and curvilinear grids. They used a range of different vegetation densities and were able to investigate the structural changes to wake turbulence patterns caused by changes in vegetation density and found that these changes had a significant effect on turbulence statistics and flow resistance.…”
mentioning
confidence: 99%
“…King et al (2012) propose a new k − ε turbulence model for inclusion in a Computational Fluid Dynamics (CFD) model that takes the effects of vegetation into account. Alternatively, Stoesser et al (2010) directly simulated flow through vegetation stems using Large Eddy Simulation.…”
Section: Modelling Vegetationmentioning
confidence: 99%